Pandangan al-Qur’an tentang Makna Jâhilîyah Perspektif Semantik - Romziana, Luthviyah (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2014)
This article will examine the meaning of the word in the Koran jâhilîyah mentioned as many as 24 verses in 17 letters with various forms of the semantic approach. This approach is an option given the existence of this word has been around since pre-islamic Arab past, as evidenced by the presence of all jâhilîyah lyric. In addition, the commentators also provide a diverse meaning to the word. Ibn Jarîr al-Tabarî that in fact as a classical commentators, stating that the meaning of the word refers jâhilîyah person who has committed a disgraceful act or any person who commits sin intentionally. While Sayyid Qutb see it as the opposite of ‘ilm and ma‘rifah. In view of Quraish Shihab is jâhilîyah is not only opposed to the word ‘ilm but also in the sense of losing control of himself, so that actors do things that are not fair, either at the instigation of appetite, temporary interests, or parochialism. Many differences of opinion about the meaning of the word jâhilîyah, interesting to study further with semantics as analysis approach",